1994
DOI: 10.1159/000187991
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan Chondroitin Sulphate Prevents Loss of Ultrafiltration during Peritoneal Dialysis in Rats

Abstract: We evaluated the effect of 6 days of intraperitoneal saline infusion on peritoneal peroxidation and permeability in rats. Peroxidation of the peritoneum as measured by malondialdehyde concentration in the omentum was increased and there was a concomitant augmented membrane permeability to glucose and resulted in a loss of ultrafiltration. In vitro experiments with mesothelial cells showed that glycosaminoglycan chondroitin sulphate appears to act as a scavenger of free radicals and so protects the mesothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Acute peritonitis is the strong inflammatory impulse in PD patients. Previously we demonstrated that supplementation of the dialysis fluid with chondroitin sulfate [17] , hyaluronan [18] or N -acetylglucosamine, which is a precursor for synthesis of glycosaminoglycans [19] , reduce the systemic and intraperitoneal inflammation in experimental animals undergoing chronic dialysis. Similar observations were described in PD patients treated chronically with heparin, which was injected daily into the dialysis bag [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Acute peritonitis is the strong inflammatory impulse in PD patients. Previously we demonstrated that supplementation of the dialysis fluid with chondroitin sulfate [17] , hyaluronan [18] or N -acetylglucosamine, which is a precursor for synthesis of glycosaminoglycans [19] , reduce the systemic and intraperitoneal inflammation in experimental animals undergoing chronic dialysis. Similar observations were described in PD patients treated chronically with heparin, which was injected daily into the dialysis bag [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Another different approach to explain the rise of plasma GAGs comes from the evidence that some of these molecules possess antioxidant activity capable of inhibiting lipid peroxidation (Foschi et al, 1990;Arai et al, 1999;Albertini et al, 2000). The use of these compounds as therapeutic agents showed some positive results both in human and in experimental animal models (Breborowicz et al, 1994;Beren et al, 2001;Campo et al, 2003a,b). The present study was designed to evaluate the effect of treatment of HA and C4S in a rat model of acute liver injury induced by CCl 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we had shown that the addition of glycosaminoglycans (as chondroitin sulphate or hyaluronan) to the dialysis fluids prevented loss of ultrafiltration when infused repeatedly for 1 week in rats [4, 5]. Furthermore, in 1-month experiments in rats, we demonstrated that the beneficial effect of hyaluronan used ‘chronically’ as an additive to the dialysis fluid may be related both to its accumulation in the peritoneal interstitium, thus changing the permselectivity of that membrane, and also to the suppression of the dialysis-induced intraperitoneal inflammation [6].…”
Section: Introductionmentioning
confidence: 99%